The last high : a thriller - Kalla, Daniel (Simon and Schuster Canada, a division of Simon & Schuster, Inc., 2020)
"One night, Dr. Julie Rees is stunned when the emergency room she works at is flooded with teenagers suffering from life-threathening drug overdoses. The patients were all at the same party, and Julie soon recognizes that these aren't typical cases. So does Detective Anson Chen, assigned to investigate what happened. Julie, who is also a toxicologist, suspects the teens took--or were given--fentanyl or a fentanyl derivative. But why did they succumb so quickly? Julie and Anson begin to try to track down whoever supplied the drugs. But when other people with the same disturbing overdose symptoms begin showing up in the ER--and the morgue--Julie starts to realize that something extremely disturbing is happening on the streets of Vancouver."--